Entropy-statistical analysis of the efficiency of cycles of refrigeration units of household refrigerators - Yu. V. Kudrov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The aim of the work is to determine the thermodynamic efficiency of the modernized refrigeration unit of a household refrigerator compared to the basic model using the entropystatistical method.Method. В ходе работы при проведении исследований применен научный метод системного анализа, а также энтропийно-статистический метод термодинамического анализа при определении эффективности холодильного цикла бытового холодильника.Result. The analysis of the distribution of energy costs to compensate for the production of entropy by the nodes of the refrigeration unit is carried out. This analysis allows us to visually assess the energy losses in the cycle of a household refrigerator. The analysis was carried out for the most popular refrigerants R134a and R600a when used in household refrigerators. Based on the calculations carried out, comparative diagrams of energy losses in cycle processes are constructed. The entropy-statistical analysis of the thermodynamic efficiency indicators of the cycle confirms the advantages of the modernized refrigeration unit of the household refrigerator.statistical method.Conclusion. In the course of the work, it was confirmed that the use of an upgraded refrigeration unit will reduce the total energy costs, and the chosen research method will visually assess the energy losses for the elements of the refrigeration unit cycle.